2016
DOI: 10.1002/anzf.1187
|View full text |Cite
|
Sign up to set email alerts
|

The Utility (or Not) of Self‐Report Instruments in Family Assessment for Child and Adolescent Conversion Disorders?

Abstract: Children and adolescents with conversion disorders and their families are challenging to understand and challenging to treat. This study examined whether self‐report instruments are a useful adjunct to family and individual assessment. A total of 57 children and adolescents diagnosed with conversion disorders and 57 sex‐ aged‐matched controls, along with their parents, completed the Strength and Difficulties Questionnaire, Child Behaviour Checklist, Depression Anxiety and Stress Scales, Somatic and Psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…By definition, it also implies family willingness to entertain psychological approaches to their child’s symptoms. Rates of reported psychological comorbidity at presentation are low (table 1) but this may reflect previously-described under-reporting of psychological symptoms in FND 31 32. Although functional neurological symptoms almost invariably initially present to paediatricians, successful treatment involves collaboration between physical and mental health teams where possible 33.…”
Section: Discussionmentioning
confidence: 94%
“…By definition, it also implies family willingness to entertain psychological approaches to their child’s symptoms. Rates of reported psychological comorbidity at presentation are low (table 1) but this may reflect previously-described under-reporting of psychological symptoms in FND 31 32. Although functional neurological symptoms almost invariably initially present to paediatricians, successful treatment involves collaboration between physical and mental health teams where possible 33.…”
Section: Discussionmentioning
confidence: 94%
“…Another factor not considered in the studies concerns the validity of measures of self-reported mental health symptoms in this population. These measures may not be useful in detecting mental health problems in children with MUS [55] and thus professional clinical diagnoses are likely to be the gold standard in the MUS population.…”
Section: Association Between Measures Of Mental Health and Alexithymiamentioning
confidence: 99%
“…To a child or adolescent, it may seem that the doctor is suggesting that ‘it’s all in my head’ or that ‘I’m psycho’, ‘going off my head’, or ‘putting it on’ – that is, suffering from a severe form of craziness or severe mental illness. To complicate matters, children/adolescents with PNES typically do not perceive themselves to be anxious, depressed or emotionally distressed ( Kozlowska, Cruz, et al, 2016 ), so the implication of PNES as ‘psychological’ appears disconnected from the children/adolescents’ personal stories and also from their somatic experiences of the ‘seizures’ (and the associated non-specific somatic symptoms) as a disturbance of the body. Not surprisingly, patients and their families are frequently offended and find the diagnosis difficult to accept.…”
Section: Introductionmentioning
confidence: 99%